Artificial Intelligence and Its Impact on Business Competition: A Review of Business Law in Indonesia - Dimas Dwi Arso (Contemporary Issues on Indonesian Social Justice and Legal Reform, 2025)
This paper aims to explore the impact of artificial intelligence on business competition and the corresponding legal and regulatory framework in Indonesia. The research employs a comprehensive literature review and policy analysis to examine the current state of AI adoption in the business sector, the associated challenges and opportunities, and the existing legal and regulatory landscape. The findings indicate that the use of AI-powered technologies can significantly affect business competitiveness, leading to both disruptions and advancements. However, the legal and regulatory framework in Indonesia has not kept pace with the rapid technological changes, posing challenges for businesses in navigating the complex and evolving landscape. To address these issues, the study recommends the establishment of collaborative platforms for ongoing dialogue and knowledge-sharing among government, industry, and academia. These platforms would facilitate the exchange of information, insights, and best practices, enabling the development of a more responsive and adaptable legal and regulatory framework. Additionally, the research highlights the importance of implementing robust workforce development initiatives to address skills gaps and ensure the effective and sustainable adoption of AI technologies within businesses. Overall, this study provides valuable insights for policymakers, business leaders, and industry stakeholders in understanding the impact of AI on business competition and the critical need for a comprehensive and collaborative approach to legal and regulatory frameworks in Indonesia.